Los últimos relatos de Carlos Carrión - Ferrer, Carlos (2020)
Th is text describes the last three books of the narrative production of the writer Carlos Carrión: El teniente y su cerdo de confi anza, El Colt 45 de Caín y Una chica dormida en un caballo. If his narrative work is based on four characters: humor, irony, love and woman, in these volumes we fi nd a use of humor and irony as tools to make a critique of a society incapable of any eff ort to overcome the extraordinary, product of the surprise that Carrión introduces in the arguments. Th e Ecuadorian author portrays the bitter reality and satirizes the hypocrisy that surrounds it. Similarly, the thematic presence of love and women in Carrión’s prose is reviewed, since he is one of the best exponents of the conjugation between sensuality, eroticism and seduction.